2021
DOI: 10.1002/gcc.23015
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency: The what, how and why it is important

Abstract: The mismatch repair system is a major pathway that functions in the maintenance of genomic integrity. It is involved in mitotic and meiotic recombination, apoptosis, immunoglobulin gene rearrangement, somatic hypermutation, and other processes. Deficiencies in mismatch repair give rise to hypermutability and the phenomenon called microsatellite instability. Detection of deficient mismatch repair function or microsatellite instability is used diagnostically, predictively, and prognostically. Specifically, defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The discordance rate shows some mild variation, with colorectal tumors and urothelial tumors being the lowest and neuroendocrine and prostate neoplasms being the highest. However, this variation was not significant (Research Question 2), and it did not deviate from the reported rates of concordance in the literature [ 1 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The discordance rate shows some mild variation, with colorectal tumors and urothelial tumors being the lowest and neuroendocrine and prostate neoplasms being the highest. However, this variation was not significant (Research Question 2), and it did not deviate from the reported rates of concordance in the literature [ 1 ].…”
Section: Discussionmentioning
confidence: 64%
“…It is a highly evolutionary conserved system. When the MMR system is deficient, deleterious DNA damage accumulates, which results in an increased number of mutations in the cell and can result in neoplasia [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of a mutL mutant in prokaryotes is a dramatic increase in mutation frequency ( Schaaper, 1993 ). This is expanded in eukaryotes by a dramatic increase in cancers, such as in Lynch syndrome ( Olave and Graham, 2021 ). The pronounced reduction in recombinational switching to background levels in the vlsE gene in the absence of MutL ( Figure 2 and Supplementary Figures 2 , 3 ) was surprising, especially because deletion of key interacting partner, MutS, did not affect either the switching frequency or the infectivity of mutS spirochetes in immunocompetent mice ( Dresser et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…MSI is defined as a small alteration in the number of short repetitive sequences, most commonly mononucleotide repeats. MSI arises from defects in postreplicative mismatch repair (MMR), and only becomes detectable after multiple cellular divisions (Boland & Goel, 2010 ; Pecina‐Slaus et al , 2020 ; Olave & Graham, 2021 ; Randrian et al , 2021 ). DNA polymerases replicating repetitive sequences are prone to slippage, leading to extrahelical loops in the replicated DNA.…”
Section: Introductionmentioning
confidence: 99%
“…What makes specifically TA repeats unique in this context remains unclear. The observation was unexpected on yet another level: MSI caused by MMR deficiency typically leads to an alteration of mononucleotide repeats, usually shortening by a few repeat units, and not a major expansion (Hoang et al , 1997 ; Pecina‐Slaus et al , 2020 ; Olave & Graham, 2021 ; Randrian et al , 2021 ). A subset of MMR proteins was instead found to act pathologically in the expansion of trinucleotide repeats, underlying syndromes such as Fragile X or Huntington's disease (Schmidt & Pearson, 2016 ; Iyer & Pluciennik, 2021 ; Neil et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%